2008
DOI: 10.1002/pon.1505
|View full text |Cite
|
Sign up to set email alerts
|

A randomized control trial of a supervised versus a self‐directed exercise program for allogeneic stem cell transplant patients

Abstract: These results demonstrate that allogeneic transplant patients derive functional benefits from short-term exercise training regardless of how the training program is supervised. Determining (1) the reasons for the low participation rate (28%), (2) the patient-preferred characteristics of each exercise supervision style and (3) how best to match patient preference to exercise supervision style remain significant issues in this area of patient delivery services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 28 publications
4
78
1
2
Order By: Relevance
“…19,20 The 6-min walk test is a submaximal performance test that reflects the tasks of daily living and has previously been used in hematological cancer populations. 3,9 Patients were advised to walk back and forth down a hallway as fast as possible for 6 min. The 6-min walk distance (6MWD) was assessed in meters (m).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 The 6-min walk test is a submaximal performance test that reflects the tasks of daily living and has previously been used in hematological cancer populations. 3,9 Patients were advised to walk back and forth down a hallway as fast as possible for 6 min. The 6-min walk distance (6MWD) was assessed in meters (m).…”
Section: Discussionmentioning
confidence: 99%
“…7 Since this review, six new randomized controlled trials have been published, supporting these findings; some studies showed strong effects for body composition as well as weaker but promising effects for cardiorespiratory fitness, fatigue, muscle strength, physical functioning and quality of life. [8][9][10][11][12][13] Nevertheless, many questions remain unanswered regarding exercise interventions in HCT patients. Additional evidence is required to determine the optimal exercise recommendation, with respect to amount, type, intensity and time point for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…We located 17 publications from 13 studies, 39,40,52-66 8 of which 39,40,53,54,56,[63][64][65] were RCTs. Only two included a large population sample (nX100).…”
Section: Adultsmentioning
confidence: 99%
“…Furthermore, maintaining some degree of physical activity attenuates the loss of, and can even improve, functional capacity PAGAC, 2008;Segal et al, 2003). Intervention studies with breast cancer survivors have demonstrated that physical activity can significantly decrease fatigue, both during treatment Mock et al, 2005;Pinto et al, 2000) and after treatment (Burnham & Wilcox, 2003;Granger et al, 2011;Shelton et al, 2009;Wilson et al, 2005). There have been fewer studies conducted with nonbreast cancer survivors, although there is some evidence that physical activity also reduces CRF in other cancer survivors, notably those with prostate cancer (Battaglini, 2011;Cramp & Daniel, 2008;Fong et al, 2012;Keogh & MacLeod, 2012;Monga et al, 2007).…”
Section: Physical Healthmentioning
confidence: 99%
“…For example, Shelton et al (2009) conducted an intervention study with haematological cancer survivors comparing supervised with self-directed groups, and found that the supervised group showed a greater decrease in fatigue, although this difference was not statistically significant. Additionally, a meta-analysis of RCTs reported that supervised aerobic programmes were significantly more successful in reducing CRF than home-based aerobic programmes in breast cancer survivors during treatment (Velthius et al, 2010), although there were not enough studies with prostate cancer survivors to draw conclusions for this population.…”
Section: Supervised Versus Self-directedmentioning
confidence: 99%